THE TWO SINGLE NUCLEOTIDE POLYMORPHISM HAPLOTYPES ON CHROMOSOME 15 OF THE HERC2 AND OCA2 GENES OF THE COLOR VARIATION OF THE HUMAN EYE IN A SAMPLE OF IRAQI POPULATION - N., Tabarek M.; Alkazaz, A. K. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to identify the role of the single nucleotide polymorphism genes on the contrast of three groups (Dark-Brown, hazel and blue) of human eye color among a sample of Iraqi people specifically single nucleotide polymorphism (SNPs); the rs12913832 of HERC2 gene and the rs1800407 of OCA2 gene, for 90 human blood samples of different people were collected from College of Science, University of Baghdad and also people from different areas of Baghdad, Iraq. These SNPs were analyzed using quantitative real-time PCR (qPCR). The results of the rs12913832 and rs1800407 genotype showed significant differences (p